EFFECT OF HARIRING KABAYAN INSTRUMENTAL MUSIC THERAPY ON PAIN AND ANXIETY LEVEL IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Arip Rahman; Bedjo Santoso; Sudirman Sudirman (Belitung Raya Foundation, Indonesia, 2018)
Background: Death due to acute myocardial infarction (AMI) continues to increase every year. Efforts to prevent AMI complications through the control of pain and anxiety with the approach of classical music therapy have been widely practiced, but the approach through local music has not been much done when transcultural nursing theory emphasizes the importance of cultural approaches in nursing care, while Indonesia has a lot of local music that is a cultural potential which needs to be developed. Objective: This study aims to know the effect of Hariring Kabayan instrumental music therapy in reducing pain and anxiety of AMI patients after 24 hours of CICU admission. Methods: This was a quasi-experimental study with pretest-posttest control group design. There were 32 participants selected using consecutive sampling, which 16 assigned in an experiment group and a control group. Hariring Kabayan therapy was played at 60 BPM using headphones connected to the MP3 player for 30 minutes. Numerical Pain Rating Scale (NPRS) was used to measure pain and Numerical Rating Scale Anxiety (NRS-A) was used to measure anxiety. Data were analyzed using Paired t-test and Independent t-test. Result: Hariring Kabayan instrumental music therapy given for 30 minutes gave a significant change on pain in the respondents (p = 0.005), but it did not give a significant change on anxiety (p = 0.053), with significant value of 0.05. Conclusion: Hariring Kabayan instrumental music therapy is effective in reducing pain in AMI patients but ineffective in anxiety reduction.